The Question of the Legal Consciousness of a Society in Transition of Development of Russia: the Theoretical Aspect - Vladimir Valentinovich Kozhevnikov; Anastasia Evgenievna Cherednichenko (Budapest International Research and Critics University, 2020)
The relevance of this scientific article is determined by the importance of legal consciousness in all spheres of social life in Russia in general and at the transitional stage of its development in particular, because it, acting as a subjective factor, largely determines the direction of the social life of the fatherland. The purpose is to analyze the most essential features of public legal consciousness in the transitional period of the development of Russia and to show its significance for the further development of Russian society. Results: in the course of the conducted scientific research it became clear that the public legal consciousness of the transitional stage of Russian society, firstly, is extremely important for the development of the latter, for all its spheres; secondly, it is characterized by fragmentation, contradictoriness and radicalism; thirdly, some tendencies in the content of such legal consciousness are associated with legal idealism and legal nihilism; Fourthly, it is influenced by a whole system of factors, including, in particular, the ill-conceived policy of our state, which, in general, does not reasonably ignore its significance. Conclusion: it is noted, firstly, that modern Russian society, which is at a transitional stage of its development, is characterized by many different contradictions, among which there is also such a bizarre interweaving of legal nihilism and legal idealism, which together form a bleak picture of legal lack of culture; secondly, it is necessary to overcome the imbalance between the autonomous legal consciousness of individuals and public legal consciousness.